Demethoxycurcumin in combination with ultraviolet radiation B induces apoptosis through the mitochondrial pathway and caspase activation in A431 and HaCaT cells - Yong Xin; Qian Huang; Pei Zhang; Wen Wen Guo; Long Zhen Zhang; Guan Jiang (Tumor Biology)
Photodynamic therapy is widely used in the clinical treatment of tumors, especially skin cancers. It has been reported that the photosensitizer curcumin, in combination with ultraviolet radiation B, induces HaCaT cell apoptosis, and this effect may be due to the activation of caspase pathways. In this study, we examined the photodynamic effects of demethoxycurcumin, a more stable analogue of curcumin, to determine whether it could induce apoptosis in skin cancer cells. We investigated the effects of a combination of ultraviolet radiation B and demethoxycurcumin on apoptotic cell death in A431 and HaCaT cells and determined the molecular mechanism of action. Our results showed increased apoptosis with a combination of ultraviolet radiation B with demethoxycurcumin, as compared to ultraviolet radiation B or demethoxycurcumin alone. The combination of ultraviolet radiation B irradiation with demethoxycurcumin synergistically induced apoptotic cell death in A431 and HaCaT cells through activation of p53 and caspase pathways, as well as through upregulation of Bax and p-p65 expression and downregulation of Bcl-2, Mcl-1, and nuclear factor-κB expression. In addition, we found that reactive oxygen species significantly increased with treatment, and mitochondrial membrane potential depolarization was remarkably enhanced. In conclusion, our data indicate that demethoxycurcumin may be a promising photosensitizer for use in photodynamic therapy to induce apoptosis in skin cancer cells.